Tingkat Tingkat Pengetahuan Siswi Jurusan Farmasi Tentang Penanganan Nyeri Menstruasi Di SMK Muhammadiyah 3 Yogyakarta: Tingkat Pengetahuan Siswi Jurusan Farmasi Tentang Penanganan Nyeri Menstruasi Di SMK Muhammadiyah 3 Yogyakarta - Trilestari (Politeknik Kesehatan Bhakti Setya Indonesia, 2023)
Menstrual pain is abdominal pain that comes from uterine cramps and occurs during menstruation. Pain during menstruation occurs due to increased levels of prostaglandins. The impact that occurs if menstrual pain is not handled properly is the disruption of daily life activities. The study aims to determine the level of knowledge about the management of menstrual pain in female students majoring in Pharmacy at SMK Muhammadiyah 3 Yogyakarta. This research is a qualitative descriptive study with a survey design. Subjects and population in this study were students majoring in Pharmacy at SMK Muhammadiyah 3 Yogyakarta grades 10 to 12 as many as 60 students. The sampling technique used was total sampling with the research variable being the level of knowledge of Pharmacy students regarding the management of menstrual pain. The level of knowledge is measured by looking at the ability of students to answer the questionnaire answers were then classified into 3 categories, namely good, sufficient and lacking. The results showed that the level of knowledge about handling menstrual pain in female students majoring in Pharmacy at SMK Muhammadiyah 3 Yogyakarta was in the good category as many as 37 respondents (61,1%), sufficient category 10 respondents (16,6%), poor category 13 respondents (21,6%).